Monitoring dan Evaluasi Kebijakan Lahan Gambut Untuk Mencegah Tragedy of The Common di Provinsi Kalimantan Tengah - Fauzi, Erinda Alfiani; Yanur, Murniyati; Irwan, Andi Ilmi Utami (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
Peatlands in Central Kalimantan Province have been used in community life as a place to live and a place to farm so that they can trigger the tragedy of the common. Its use is not monitored and evaluated, and the government has issued several policies to prevent this from happening—the tragedy of the commons peatlands. Monitoring and evaluating policies are the process of monitoring, observing, and assessing the government's implementation. This study uses a qualitative descriptive method. The results of this study show that the government's policies have been very effective in suppressing the tragedy of the common peatlands of Central Kalimantan Province. However, the evaluation results show the need for socialization and policy matching between the centre and regions so that implementation is right on target and follows local wisdom in Central Kalimantan.